Endonasal CNS Delivery System for Blood-Brain Barrier Impermeant Therapeutic Oligonucleotides Using Heterotopic Mucosal Engrafting - Pawar, Grishma (Front Pharmacol, 2021)
The most significant obstacle in the treatment of neurological disorders is the blood-brain barrier (BBB), which prevents 98% of all potential neuropharmaceuticals from reaching the central nervous system (CNS). Brain derived neurotrophic factor (BDNF) is one of the most intensely studied targets in Parkinson’s disease (PD) as it can reverse disease progression. BDNF AntagoNAT’s (ATs) are synthetic oligonucleotide-like compounds capable of upregulating endogenous BDNF expression. Despite the significant promise of BDNF AT therapies for PD, they cannot cross the blood-brain barrier (BBB). Our group has developed an innovative endonasal heterotopic mucosal grafting technique to provide a permanent method of permeabilizing the BBB. This method is based on established endoscopic surgical procedures currently used in routine clinical practice. Our overall goal for the study was to investigate the distribution and efficacy of BDNF AT’s using an extra-cranial graft model in naïve rats using the innovative heterotopic mucosal engrafting technique. BDNF AT cationic liposomes (ideal size range 200–250 nm) were developed and characterized to enhance the delivery to rat brain. Uptake, distribution and transfection efficiency of BDNF AntagoNAT’s in saline and liposomes were evaluated qualitatively (microscopy) and quantitatively (ELISA and AT hybridization assays) in RT4-D6P2T rat schwannoma cells and in naïve rats. In vivo therapeutic efficacy of BDNF AT’s encapsulated in liposomes was evaluated in a 6-OHDA toxin model of PD using western blot and tyrosine hydroxylase immunohistochemistry. Using complimentary in vitro and in vivo techniques, our results demonstrate that grafts are capable of delivering therapeutic levels of BDNF ATs in liposomes and saline formulation throughout the brain resulting in significant BDNF upregulation in key end target regions relevant to PD. BDNF AT liposomes resulted in a better distribution in rat brain as compared to saline control. The delivered BDNF AT’s encapsulated in liposomes also conferred a neuroprotective effect in a rat 6-OHDA model of PD. As a platform technique, these results further suggest that this approach may be utilized to deliver other BBB impermeant oligonucleotide-based therapeutics thereby opening the door to additional treatment options for CNS disease.